Compression Sleeves Increase Tissue Oxygen Saturation But Not Running Performance - Ménétrier, A.; Mourot, L.; Bouhaddi, M.; Regnard, J.; Tordi, N. (International Journal of Sports Medicine, 2011)
The purpose of this study was to determine the effects of calf compression sleeves on running performance and on calf tissue oxygen saturation (StO2) at rest before exercise and during recovery period. 14 moderately trained athletes completed 2 identical sessions of treadmill running with and without calf compression sleeves in randomized order. Each session comprised: 15 min at rest, 30 min at 60% maximal aerobic velocity determined beforehand, 15 min of passive recovery, a running time to exhaustion at 100% maximal aerobic velocity, and 30 min of passive recovery. Calf StO2 was determined by near infra-red spectroscopy and running performance by the time to exhaustion. Compression sleeves increased significantly StO2 at rest before exercise (+ 6.4±1.9%) and during recovery from exercise (+ 7.4±1.7% and + 10.7±1.8% at 20th and 30th min of the last recovery period, respectively). No difference was observed between the times to exhaustion performed with and without compression sleeves (269.4±18.4 s and 263.3±19.8 s, respectively). Within the framework of this study, the compression sleeves do not improve running performance in tlim. However the StO2 results argue for further interest of this garment during effort recovery.
Keywords: external compression; near infra-red spectroscopy; recovery; exhaustion